2016
DOI: 10.1039/c6mb00420b
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomics of Indian women with polycystic ovary syndrome using 1H NMR coupled with a pattern recognition approach

Abstract: Polycystic ovary syndrome (PCOS) is one of the most commonly occurring metabolic and endocrinological disorders affecting women of reproductive age. Metabolomics is an emerging field that holds promise in understanding disease pathophysiology. Recently, a few metabolomics based studies have been attempted in PCOS patients; however, none of them have included patients from the Indian population. The main objective of this study was to investigate the serum metabolomic profile of Indian women with PCOS and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Comparisons to previous studies of plasma metabolomics profiles in PCOS are limited by small sample sizes, further diluted by subgroups of BMI and insulin resistance status (14, 15, 21), as well as by different analytic techniques, including less-sensitive nuclear magnetic resonance or nontargeted metabolomics and lack of BMI matching in control groups (13, 14, 16, 18). Most prior studies used the Rotterdam criteria for PCOS and did not restrict study participants to those with the more severe phenotype of oligomenorrhea and anovulation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Comparisons to previous studies of plasma metabolomics profiles in PCOS are limited by small sample sizes, further diluted by subgroups of BMI and insulin resistance status (14, 15, 21), as well as by different analytic techniques, including less-sensitive nuclear magnetic resonance or nontargeted metabolomics and lack of BMI matching in control groups (13, 14, 16, 18). Most prior studies used the Rotterdam criteria for PCOS and did not restrict study participants to those with the more severe phenotype of oligomenorrhea and anovulation.…”
Section: Discussionmentioning
confidence: 90%
“…Genomic (911), proteomic (11, 12), and metabolomic (1320) approaches to study the pathogenesis of PCOS have implicated various pathways, including oxidative stress, immune function, and lipid metabolism. However, the activation of these pathways might reflect the high prevalence of obesity in women with PCOS, rather than the underlying pathogenesis of insulin resistance associated with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…This is important as we would wish to develop diagnostic markers that could ultimately be measured in blood samples rather than tissue specimens. Recent evidence from patients with metabolic disturbance associated with polycystic ovary syndrome confirms that it is indeed possible to detect changes in circulating amino acids and carbohydrates in serum using an NMR approach[50]. In addition, give the important contribution of exercise to management of NAFLD[51] and links between skeletal muscle activity and hepatic metabolism[52,53] it would be important to assess the contribution of sarcopenia in advanced cirrhosis to the hepatic metabolome.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS has been reported to be associated with impaired lipid metabolism, and a dramatic increase in fatty acids leads to significant lipid profile changes in PCOS patients. [ 6 15 16 17 ] Fatty acids are an important energy source in the body and provide energy through β-oxidation. Studies have shown that PCOS is related to a decreased fatty acid oxidation capacity, and as a result, excessive fatty acids accumulate in the body causing lipotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics is a powerful tool for identifying useful biomarkers in the diagnosis of PCOS and for studying its pathogenesis. Metabolomic studies of PCOS plasma samples have been performed using hydrogen-1 nuclear magnetic resonance,[ 5 6 ] gas chromatography-mass spectrometry (GC-MS),[ 7 ] and liquid chromatography-mass spectrometry (LC-MS). [ 8 ] Multiple metabolic disorders have been observed in PCOS, including the metabolism of steroid hormones, carbohydrates, amino acid, and lipids.…”
Section: Introductionmentioning
confidence: 99%